Persepsi dan Partisipasi Publik dalam Upaya Pemanfaatan Museum Situs Sangiran Berbasis Masyarakat - Huda, M. Amirul (Humanis, 2017)
Perception and participation is important to know as the management control managers in formulating and deciding policy. The Purposes of the research is to knowing the level of perception and participation of communities in the Sangiran Site on utilization of community-based Sangiran Museum site, then knowing the role and efforts of the government in the community-based program. It is based on the idea that the success of efforts on utilization the Sangiran Museum site does not only depend on the government, but the extent to which local communities are involved in these activities. The Data aggregation techniques in this research were used observation, interviews, questionnaires, and literature study. Besides that this research was used some theory and analysis and in explaining the problems of researchers, namely the theory of perception, participation and management, as well as used quantitative descriptive analysis .
Keywords: perception, participation of the public, the Sangiran Museum' s Site utilization in community based